STUDI KOMPARATIF METODE PENENTUAN HARGA POKOK PRODUKSI PADA PERUSAHAAN MULTINASIONAL YAITU COCA-COLA DI NEGARA BERINFLASI TINGGI DAN RENDAH - Mutiara, Indah; Kotten, Karan I.; Bere, Meilinda C. C.; Epa, Mikhael B. M.; Rabbani, Muhammad Asyraf K.; Ranggi, Oktavianus S.; Marman, Patrik R.; Endi, Paulinus V.; Karfin, Skolastika Y.; Korolulu, Yunus (Universitas Nusa Cendana, 2025)
This study aims to compare the cost of production determination methods used by multinational companies operating in countries with high and low inflation rates. The research employs a case study approach involving coca-cola as multinational companies operating in two countries with different inflation characteristics. Data were collected through trend analysis, content analysis, disclosure evaluation, in-depth audit risk identification, and analysis of the companies' financial statements. The results of the study show that Inflation and translation reflect significant changes in prices, purchasing power, and exchange rate fluctuations during the reporting period. This research contributes to the understanding of how inflation affects the cost accounting policies of multinational companies and highlights the importance of flexibility in choosing cost of production determination methods in different economic environments.